Germline MLH1 Mutations Are Frequently Identified in Lynch Syndrome Patients With Colorectal and Endometrial Carcinoma Demonstrating Isolated Loss of PMS2 Immunohistochemical Expression. (August 2015) - Dudley, Beth; Brand, Randall E.; Thull, Darcy; Bahary, Nathan; Nikiforova, Marina N.; Pai, Reetesh K.
Abstract : Current guidelines on germline mutation testing for patients suspected of having Lynch syndrome are not entirely clear in patients with tumors demonstrating isolated loss of PMS2 immunohistochemical expression. We analyzed the clinical and pathologic features of patients with tumors demonstrating isolated loss of PMS2 expression in an attempt to (1) determine the frequency of germline MLH1 and PMS2 mutations and (2) correlate mismatch-repair protein immunohistochemistry and tumor histology with germline mutation results. A total of 3213 consecutive colorectal carcinomas and 215 consecutive endometrial carcinomas were prospectively analyzed for DNA mismatch-repair protein expression by immunohistochemistry. In total, 32 tumors from 31 patients demonstrated isolated loss of PMS2 immunohistochemical expression, including 16 colorectal carcinomas and 16 endometrial carcinomas. Microsatellite instability (MSI) polymerase chain reaction was performed in 29 tumors from 28 patients with the following results: 28 tumors demonstrated high-level MSI, and 1 tumor demonstrated low-level MSI. Twenty of 31 (65%) patients in the study group had tumors demonstrating histopathology associated with high-level MSI. Seventeen patients underwent germline mutation analysis with the following results: 24% with MLH1 mutations, 35% with PMS2 mutations, 12% with PMS2 variants of undetermined significance, and 29% with no mutations in either MLH1 or PMS2 . Three of the 4 patients with MLH1 germline mutations had a mutation that results in decreased stability and quantity of the MLH1 protein that compromises the MLH1-PMS2 protein complex, helping to explain the presence of immunogenic but functionally inactive MLH1 protein within the tumor. The high frequency of MLH1 germline mutations identified in our study has important implications for testing strategies in patients suspected of having Lynch syndrome and indicates that patients with tumors demonstrating isolated loss of PMS2 expression without a germline PMS2 mutation must have MLH1 mutation analysis performed.